PROFILE OF HIGH ALERT MEDICATION STORAGE AT PHARMACY X IN MAJALENGKA REGENCY - Marlindasari, Liska; Meilinda, Vivi (Jurnal Health Sains, 2025)
Look Alike Sound Alike (LASA) drugs are drugs that have similarities in physical appearance, name, or pronunciation that can cause medication errors. Improper storage of LASA drugs is one of the main risk factors for dispensing errors in pharmacies. This study aims to evaluate the appropriateness of LASA storage at Pharmacy X based on Ministry of Health Regulation No. 73 of 2016. This study used a descriptive method with an observational and analytical approach based on the guidelines of Permenkes No. 73 of 2016. The study sample included all LASA drugs available at Pharmacy X, categorized into three groups: similar pronunciation, similar packaging, and drugs with different strengths. Of the total 59 LASA drug names evaluated, it was found that 91.52% of the drug names had been stored in accordance with the standards of Minister of Health Regulation No. 73 of 2016, while 8.48% still required improvements in the storage system by labeling all LASA-categorized drugs with the "LASA" label and using the Tall Man Lettering method for drug names that have similar pronunciations. The storage of LASA drugs at Pharmacy X is generally adequate. However, careful implementation of labeling and the use of tall man lettering are still required to achieve optimal standards and prevent medication errors. Medication errors can occur if drugs are not stored properly and are not labeled or marked, allowing for mistakes to be made when dispensing medication.